Pengaruh Leverage, Profitabilitas, Thin Capitalization dan Capital Intensity terhadap Agresivitas Pajak - Debora Laurensia (Universitas Kristen Krida Wacana, 2022)
In taxation activities in Indonesia there are different significances, such as, the government and companies. The government maximizes tax levies for the properity of the people while companies jostling to tax planning to maximize profits and reduce tax payments, where taxes are one of the burdens of companies that can reduce profits. Based on these gaps, the study aims to test and analyze whether leverage, profitability, thin capitalization, and capital intensity affect aggressive taxes on the health sector listed on the Indonesia Stock Exchange for the period 2013-2020 The results of this study, the higher profitability will affect the occurrence of tax aggressiveness by focusing on company profits and the higher the debt on thin capilization is used to expand the company’s capital in running its business, in other words, the more the value of debt to the company affects the low level of aggressive tax avoidance in health sector companies. Keywords: Capital Intensity, Leverage, Profitability, Tax aggressiveness, Thin capitalizatio